The Effect of Government-Borne Value Added Tax (VAT) Incentives on Electric Car Sales in Indonesia - Putra, Surya Adi; Riyanto, Riyanto (Al-Makki Publisher, 2025)
Indonesia is a significant contributor to global greenhouse gas emissions, which contribute to global warming. To reduce emissions and achieve the net-zero emission target by 2060, Indonesia encourages the use of electric vehicles. However, sales of battery-based electric cars remain low. To increase sales, the Government provides Government-Borne Value Added Tax (VAT DTP) incentives, in addition to other fiscal and non-fiscal incentives. This study aims to analyze the influence of the VAT DTP incentive policy on electric car sales in Indonesia. The methods employed are Difference-in-Differences (DID) and Propensity Score Matching (PSM) with monthly electric car sales data from the Indonesian Motor Vehicle Industry Association (Gaikindo) for the period January 2022 to September 2024. The results of this study demonstrate that the implementation of VAT DTP incentives since April 2023 has had a significant positive effect on electric car sales. Other factors, such as first-mover advantage, promotional events, price, brand, and car specifications, also affect sales.